O endividamento público, o enriquecimento privado e o empobrecimento social em Mato Grosso - Rossi, Willian (2020)
This research presents an analysis about the public debit of Mato Grosso state in the period from 2003 to 2018 and its impacts on the materiality of the State’s social policies for the working class. For the proposed analysis, explanatory research is used as a methodology, which starts from official documents, agreement and financial statements, and goes through secondary sources, when necessary. The research presents its results divided into three sections accompanied by the final considerations. Initially, there is the historical process, which originated the concentration of land ownership, the consolidation of agribusiness in Mato Grosso and the way in which public debt was structured, starting with the division of the state in 1977. Next, the analysis of agreements of public debt in force, from 2003 to 2018, accompanied by data sources, which confirm that the main works contracts in recent years were used for the embezzlement of public money. The third section presents the impact of the public debt on the state's financial revenues, with an analysis on the application of public resources, relating those destined for capitalist accumulation with those destined for social spending, thus proving that the loans were not contracted to favor the working class, despite being the big payer of such debts. The result of the research identifies that, despite the huge investments made for capitalist accumulation, in Mato Grosso, the working class did not participate in the gains obtained by the private initiative. The concentration of income and the social inequality produced by public debt policies resulted in the social impoverishment of workers and the enrichment of a capitalist elite.